2014
DOI: 10.1134/s1063776114070097
|View full text |Cite
|
Sign up to set email alerts
|

Multicaloric effect in a solid: New aspects

Abstract: The multicaloric effect that is the result of interaction between various caloric effects has been studied theoretically. The effects attributable to the pairwise interactions of fields (piezomagnetocaloric, piezoelectrocaloric, and magnetoelectrocaloric effects) have been added to the previously known electroca loric, magnetocaloric, and elastocaloric effects that exist when the electric, magnetic, and elastic fields change. These new effects are shown to be determined by the temperature dependence of the pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 26 publications
0
14
0
4
Order By: Relevance
“…Recently, a theoretical study has shown that giant mC can be expected in ferroelectric Ba 0.5 Sr 0.5 TiO 3 10 and BaTiO 3 11. However, there are few experimental reports on caloric effects driven by multi-fields up to now12. In this paper, we report the caloric effect driven by both electric field and strain in antiferroelectric PZT films on 0.7Pb(Mg 1/3 Nb 2/3 )O 3 -0.3PbTiO 3 (PMN-PT) substrate.…”
mentioning
confidence: 99%
“…Recently, a theoretical study has shown that giant mC can be expected in ferroelectric Ba 0.5 Sr 0.5 TiO 3 10 and BaTiO 3 11. However, there are few experimental reports on caloric effects driven by multi-fields up to now12. In this paper, we report the caloric effect driven by both electric field and strain in antiferroelectric PZT films on 0.7Pb(Mg 1/3 Nb 2/3 )O 3 -0.3PbTiO 3 (PMN-PT) substrate.…”
mentioning
confidence: 99%
“…This is referred to as the multicaloric effect or multicaloric materials or sometimes also multiferroic materials (see e.g., Meng et al (2013), Starkov and Starkov (2014a), Moya et al (2014), , and Planes et al (2014)). The engineering part, required to bring these materials to efficient working devices still remains to be completed.…”
Section: Multicaloric Materialsmentioning
confidence: 98%
“…On the other hand, the induced field dH me is the proposed fictitious field that occurs spontaneously due to the application of the E field. According to Lenz's law, the strength of the induced field dH me is exactly as large as needed to account for the change in magnetization M via the well-known magneto-electric effect due to the application of E. This is also the meaning of the negative sign in (11). Therefore, at constant T and H (or zero applied magnetic field), the change dM should be zero as the effect of the applied E field on M is cancelled out by the occurrence of the induced field.…”
mentioning
confidence: 99%
“…This is achieved by replacing dH with: me app dH dH dH   (11) Relation (11) shows that the acting magnetic field on the multiferroic is a combination of the externally applied magnetic field, H app and the induced magneto-electric field, H me , where the minus sign indicates that the induced magneto-electric field is opposed to the applied field as dictated by Newton's 3 rd law, or its extension to magnetic phenomena, Lenz's law. Using (11), relation (7) should then be written as: meterms of E and H field vector components and their relationship to the sample geometry, crystal symmetry and directions of polarization and magnetization. This is particularly important when an antiferromagnetic phase exists in the multiferroic or when the sample geometry displays strong spatial variations.…”
Section: The Solutionmentioning
confidence: 99%
See 1 more Smart Citation